(untitled) (Journal of Surgical Sciences, 2019)
Objective: To determine the association of Human Epidermal growth factor Receptor2 (HER-2) with hormonal receptor status and common clinico-pathological parameters of breast carcinoma. Study Design: Cross-sectional, observational study. Place and Duration of Study: Department of Surgery, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh during the period from January 2009 to December 2009. Methodology: A total of 100 patients of female breast carcinoma with HER-2 status, hormonal receptor profile and clinico-pathological parameters were included in this study. Patient’s age, menopausal status, tumour size, lymph node status, Estrogen Receptor (ER) and Progesterone Receptor (PR) status were evaluated and their association was determined with H.ER-2 over expression using the chi-square test for analysis. Results: Of these 100 cases, mean age of diagnosis was 48 years and mean tumour size 4.4 cm. Lymph node metastases were present in 50% cases. HER-2 over-expression was seen in 29% cases, while ER and PR expression was seen in 61 % and 43% respectively. ER and PR showed inverse association (p <0.05) with HER-2 while positive association was seen with tumour size and lymph node metastases (p <0.05). No association was seen with menopausal status. Further, among 61 ER positive cases, 4 cases also HER-2 over expressed. Conclusion: The study had indicated that Her-2 may be a powerful predictor of poor prognosis as its over-expression was strongly directly associated with tumor size and lymph node involvement and inversely associated with hormonal receptor status of breast carcinoma. ER positive cases can also be HER-2 over expressed (4%), so ER status cannot be used to select tumours for evaluation of HER-2 status. As treatment modalities of ER positive and HER-2 over expressed is different, so all the patients should be studied with both receptor and treat accordingly. Journal of Surgical Sciences (2012) Vol. 16 (2) : 59-67